Evaluation of the CGIAR Research Program on Global Rice Science Partnership (GRiSP) - Breseghello, Flavio; Byerlee, Derek; Panaud, Olivier; Rerkasem, Benjavan; Sy, Aziz; Teng, Paul; Kuile, Martha Ter (CGIAR Independent Evaluation Arrangement, 2016)
The CGIAR Research Program on Global Rice Science Partnership (GRiSP), led by the International Rice Research Institute (IRRI), encompasses nearly all research at IRRI and brings together the mandates, previously separate, of three CGIAR Centers related to rice research: IRRI, AfricaRice and CIAT.